The liquidation of exile : studies in the intellectual emigration of the 1930s - Kettler, David (London : Anthem Press, 2011)
A theoretical overview and six case studies showing that the exile of intellectuals is a difficult, dependent, and fluid condition, whose achievements are dearly bought and whose endings rarely fulfill the missions informing their beginnings.
The study of intellectual exile: a paradigm -- Self-knowledge and sociology: Nina Rubinstein's exile studies -- A German subject to recall: Hans Mayer as internationalist, cosmopolitan, outsider and/or exile -- Exile as process: the case of Franz L. Neumann -- The symbolic uses of exile: Erich Kahler at Ohio State -- First letters: the liquidation of exile? -- The second wave: an autobiographical exercise.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Germans -- Foreign countries -- History -- 20th century; Exiles -- Germany -- History -- 20th century; Intellectuals -- Germany -- History -- 20th century; Political refugees -- Germany -- History -- 20th century; Germany -- Emigration and immigration -- History -- 20th century; Germany -- Intellectual life -- 20th century